Role of CD15 expression in dysplastic and neoplastic tissue of the bile duct – a potential novel tool for differential diagnosis of indeterminate biliary stricture. Issue 6 (23rd September 2016) - Walter, Dirk; Herrmann, Eva; Winkelmann, Ria; Albert, Jörg G; Liese, Juliane; Schnitzbauer, Andreas; Zeuzem, Stefan; Hansmann, Martin‐Leo; Peveling‐Oberhag, Jan; Hartmann, Sylvia
Abstract : Background and aims: CD15 is expressed by various cancer types; among these are intrahepatic and perihilar cholangiocarcinoma (CCA). The aim of this study was to elucidate CD15 expression in distal CCA as well as in dysplastic biliary tissue and to determine its prognostic significance. Methods and results: Tissue samples from patients with intrahepatic (iCCA, n = 22), perihilar (pCCA, n = 7) and distal CCA (dCCA, n = 15), who underwent surgical resection in the period from 2010 to 2015 were evaluated for CD15 expression. Tissue of synchronous lymph node metastasis ( n = 13), CCA‐associated dysplasia ( n = 20), dysplasia in intraductal biopsies ( n = 10) and benign proliferations ( n = 12), as well as inflammatory biliary lesions ( n = 28) and non‐inflammatory bile ducts ( n = 23), were evaluated equally for CD15 expression. CD15 was found to be expressed highly in iCCA (81.8%), pCCA (85.7%), dCCA (73.3%), CCA‐associated dysplasia (70.0%), dysplasia in intraductal biopsies (100%) and metastatic tissue (84.6%). CD15 expression was negative in 58 of 64 benign bile duct alterations resulting in an overall sensitivity and specificity of CD15 in CCA of 80.7 and 90.6% patients, respectively. CD15 expression was correlated significantly with a decreased overall survival in patients with CD15‐positive CCA associated dysplasia ( P = 0.003). However, CD15 expression in the invasive tumour component was not correlated with clinical outcome. Conclusion: CD15 is a sensitive and specific marker for intraepithelial and invasive neoplasias of the bile duct. Therefore, it can be helpful in the delineation of dysplastic and neoplastic biliary cells from non‐neoplastic tissue, which frequently causes a diagnostic problem in indeterminate biliary stricture.